2007
DOI: 10.1086/509925
|View full text |Cite
|
Sign up to set email alerts
|

Lower Clinical Effectiveness of Oseltamivir against Influenza B Contrasted with Influenza A Infection in Children

Abstract: Oseltamivir is much less effective against influenza B virus infection in young children, probably because of the low sensitivity of influenza B viruses to oseltamivir. The effectiveness of oseltamivir against influenza B is influenced by age and host immunity. A few oseltamivir-resistant influenza B strains were isolated before the start of oseltamivir therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
121
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(133 citation statements)
references
References 17 publications
11
121
0
1
Order By: Relevance
“…However, since recent clinical studies have shown that the antipyretic effect of OP on type A influenza is stronger than that on type B influenza, 33,34) the antipyretic effect of OP is considered to be due to not only direct pharmacological effects on thermoregulation, but also anti-influenza virus activity.…”
Section: )mentioning
confidence: 99%
“…However, since recent clinical studies have shown that the antipyretic effect of OP on type A influenza is stronger than that on type B influenza, 33,34) the antipyretic effect of OP is considered to be due to not only direct pharmacological effects on thermoregulation, but also anti-influenza virus activity.…”
Section: )mentioning
confidence: 99%
“…The licensed influenza virus neuraminidase inhibitors zanamivir and oseltamivir carboxylate are beneficial when treatment is initiated early, but this is increasingly offset by viral resistance (15)(16)(17). Despite extensive research, no vaccines are currently available for paramyxoviruses such as RSV and the HPIVs, and declining mumps vaccine uptake in several developed countries has, in conjunction with primary and secondary vaccine failures, resulted in a recent resurgence of mumps (14).…”
mentioning
confidence: 99%
“…In Japan, more than 90% of infl uenza cases in children are administered antiviral drugs, mostly oseltamivir and occasionally amantadine (Sugaya et al 2007). In this study, only 42 of 424 infl uenza patients (9.9%) did not receive antiviral drug (non-antiviral group).…”
Section: Discussionmentioning
confidence: 66%